Surface Characteristics Together With Environmental Conditions Shape Marine Biofilm Dynamics in Coastal NW Mediterranean Locations - Briand, Jean-François; Pollet, Thomas; Misson, Benjamin; Garnier, Cédric; Lejars, Marlène; Maintenay, Marine; Barry-Martinet, Raphaëlle; Portas, Aurélie; Ghiglione, Jean-François; Bressy, Christine (Frontiers in Marine Science, 2022)
Microbial colonization of artificial substrates in coastal areas, which concerns hull ships, sensors as well as plastic debris, is of huge significance to attain a rational environmental management. Some surface and environmental drivers of biofilm development have previously been described but their relative impact on the formation of biofilms remains unknown while crucial. Especially, there is no evidence of the relative importance of physical surface properties (wettability, roughness, smoothness) compared to seawater characteristics in driving biofilm abundance and diversity. In addition, few studies have considered the temporal evolution of this complex form of colonization, which often prevent to globally understand the process. Using experimental facilities in two Mediterrranean locations, a multidisciplinary approach including surface characterizations as well as seawaterquality analyses, flow cytometry and 16S rDNA metabarcoding, allowed for the identification of the main drivers of colonization for two antifouling (AF) coatings. One AF coating released copper (SPC1) while the other limit colonization thanks to physical properties, namely a low surface energy, roughness and smoothness (FRC1). Results were obtained over 75 days and compared to a control surface (PVC). Biofilm development was observed on all surfaces, with increasing density from AF coatings to PVC. Pionneer bacteria were dissimilar within all three surface types, however, communities observed on FRC1 converged toward PVC ones overtime, whereas SPC1 communities remained highly specific. A remarkably low and unique diversity was found on SPC1 during the experiment as Alteromonas accounted for more than 90% of the community colonizing this substrate until 12 days, and remained one of the co-dominant taxa of mature biofilms. Moreover, clear differences were found between geographical locations. Low nutrients and higher hydrodymanics in Banyuls bay resulted in less dense biofilms overall compared to Toulon, but also in a the slower dynamic of biofilm formation. This is illustrated by the persistence of pioneer Alteromonas but also Hyphomonadacae after 75 days on SPC1. We concluded that, even if local environmental conditions influenced the composition of biofilm communities, particular physical features may control the biofilm density but not the diversity, while copper releasing coating controlled both. In addition, it is evident from these results that sequential biofilm dynamics should carefully be considered as initial processes of formation differed from the long-term ones.